Pengaruh Transparansi dan Kompetensi Aparatur Desa terhadap Akuntabilitas Pengelolaan Dana Desa : (Studi Pada Pemerintah Desa Kecamatan Natar Kabupaten Lampung Selatan) - Yusranda Saputra; Meita Sekar Sari; Darwin Warisi (AKUNTANSI 45, 2024)
This research aims to determine the influence of Transparency and Competence of Village Officials on Accountability in Village Fund Management (study at the Village Government of Natar District, South Lampung Regency). The method used in this research is quantitative descriptive where the data processing is carried out statistically and then the data used is primary data in the form of a questionnaire. The population in this study were village officials in 26 villages in Natar District, South Lampung Regency and the sampling technique used a saturated sampling method with a total sample of 130 village officials consisting of village heads, village secretaries, general and administrative heads, financial heads and planning department. The analysis technique is carried out through validity testing, reliability testing, classical assumption testing, multiple linear regression testing and hypothesis testing. Based on the results of the analysis, it can be concluded that simultaneously Transparency and Village Apparatus Competence have a positive and significant effect on Village Fund Management Accountability and partially each variable has a positive and significant effect on Village Fund Management Accountability.